Anapisa monotonia Kiriakoff, 1963 – a junior synonym of Anapisa holobrunnea (Talbot, 1932), with new records of Arctiinae (Lepidoptera: Erebidae) from Ghana - Przybyłowicz, Łukasz; Bąkowski, Marek (Zootaxa, 2011)
Arctiinae (Lepidoptera: Erebidae) of the African continent are relatively poor studied compared to other tropical areas. Their distribution is almost completely unknown in many countries or it is based on old, unverified literature data, although some useful information can be extracted from the online database “Afromoths” (De Prins & De Prins 2011). Modern national or regional checklists covering all of the Arctiinae exist for Lesotho (Kopij 2005), Nigeria (Medler 1980), Southern Africa (Vári et al. 2002) and Madagascar (Viette 1990). Generally, revisionary works treating the whole continent concern only Arctiini (Goodger & Watson 1995) and Syntomini: Thyretina (Kiriakoff 1960, Przybyłowicz 2009). Currently more than 40 species of Arctiini (Goodger & Watson 1995) and 15 species of Thyretina (Syntomini) (Przybyłowicz 2009) are recorded from Ghana.